A lexical semantic analysis of selected verbs in Northern Sotho - Phasha, Maction Nkgoropo (Stellenbosch : University of Stellenbosch, 2008)
The main purpose of this study is to investigate the properties of selected monotransitive verbs in Northern Sotho as regard their argument structure and event structure. These Northern Sotho verbs will be examined within the general theoretical framework of Generative Lexicon Theory postulated by Pustejovsky (1996). This theory is in essence concerned with the account of word meaning as it relates to lexical semantic properties of lexical items in composition with other lexical items in a sentence. The arguments of the Northern Sotho verbs examined will include an agentive subject argument, the external argument, and a patient/theme object argument, the internal argument. In addition, a locative internal argument occurs in the sentences, which may have the status of a true argument, a shadow argument, or a default argument, in Pustejovsky’s classification of arguments. The Northern Sotho verbs examined demonstrate accomplishment events in that they entail a change of state and are telic (i.e. they have a logical culmination or endpoint). This telicity property of the verb is often the result of the occurrence of the internal arguments, i.e. the patient/theme argument and locative argument of the verb. The verb classes examined for Northern Sotho include (i) verbs of putting, (ii) verbs of removing, (iii) verbs of sending and carrying, (iv) verbs of exerting force/push/pull verbs), (v) verbs of change of possession, (vi) learn verbs, (vii) verbs of throwing, (viii) verbs of contact by impact, (ix) verbs of cutting, (x) verbs of separating and disassembling, (xi) verbs of creation and transformation, (xii) verbs of communication, (xiii) verbs of ingesting, (xiv) verbs of change of state, and (xv) verbs of motion.